A SYNTACTIC ANALYSIS OF INTERROGATIVE SENTENCES IN COLLEEN HOOVER’S REMINDERS OF HIM - Mouriena, Rekha; Nazara, Wa’özisökhi (STBA Prayoga Padang, 2024)
This syntactic analysis aimed to shed light on the constructions and the functions ofinterrogative sentences found in the novel Reminders of Him. This research is qualitative. Thewriters collected data from the novel Reminders of Him using non-participant observation(Suwartono, 2014). The data were analyzed using a distributional method (Sudaryanto, 2015;Mahsun, 2017). The findings of this research principally support the categories ofconstructions and functions of interrogative sentences set out by Greenbaum & Nelson(2012) and Seaton & Mew (2007). The researchers found; 278 wh-constructions, 204 yes/noquestion constructions, 65 declarative constructions, 6 alternative constructions, 3 tagconstructions, 2 rhetorical constructions, and 133 incomplete sentences. The writers alsofound 316 interrogative sentences function to ask for information, 307 to ask for agreement,57 to confirm something, and 11 functions to give options.